2010
DOI: 10.1111/j.1741-2358.2009.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the lubricant and the alloy on the wear behaviour of attachments

Abstract: The use of a lubricant which simulates clinical conditions is an absolute need for wear simulation because the retention force changes are influenced enormously. The change of the alloy at the Dalbo(®) -Z system did not influence the wear behaviour. As a slight decrease in retention force was recorded, it is useful for an attachment system to allow compensation with an adjustable matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…This is similar to other in vitro studies using an artificial saliva test environment, but contradictory to the findings of studies using air or water as the testing milieu . This supports the proposition that the presence of a salivary substitute is necessary to attain relevant results from wear studies . Temperature may also be important to Locator wear behavior, because of the low glass transition temperature of the nylon used in the patrix insert…”
Section: Discussionsupporting
confidence: 70%
“…This is similar to other in vitro studies using an artificial saliva test environment, but contradictory to the findings of studies using air or water as the testing milieu . This supports the proposition that the presence of a salivary substitute is necessary to attain relevant results from wear studies . Temperature may also be important to Locator wear behavior, because of the low glass transition temperature of the nylon used in the patrix insert…”
Section: Discussionsupporting
confidence: 70%
“…; Bayer et al. ). Also the convergence or divergence of implants might play a role in wear behaviour (Ludwig et al.…”
mentioning
confidence: 96%
“…A possible explanation for the faster degradation of the LAs in the oral environment observed in our study is the exposure to moisture (from saliva), which was shown to cause physical and/or chemical changes, such as increase in creep, flexibility, and stress relaxation, and reduction in stiffness, tensile strength, flexural strength, corrosion, and microcracking of the nylon components in previous investigations . In addition, in vitro studies have shown that hypochlorite‐based denture cleansers have a strong detrimental effect on the LAs nylon inserts, and may also interfere with the retentive properties of ball attachments . Although, we did not monitor the use of cleansers in this study, the nylon inserts are expected to need replacement more frequently than metallic ball attachments due to the faster loss of retention observed.…”
Section: Discussionmentioning
confidence: 50%